Minimally Invasive Surgical Technique for the Extraperitoneal Fixation of Acetabulum Fracture: Technical Feasibility Study in Cadaver - Piia Suomalainen; Essi Honkonen; Sami Nurmi; Anu Välikoski; Antti Siiki (Advances in Orthopedics)
Conclusions: A minimally invasive full endoscopic procedure for acetabular fractures offers significant benefits over traditional open surgery due to faster rehabilitation, potentially less blood loss, and fewer wound complications. According to our initial experiences with cadavers, this minimally invasive method appears promising in terms of superior visibility and easier access to the otherwise narrow and difficult fracture site in the pelvic region compared to open surgery. Furthermore, this minimally invasive method seems feasible for exact plate placement under combined endoscopic and fluoroscopic visual control. The usefulness of this novel method in the minimally invasive treatment of acetabular fractures in real life, especially considering the practicality of proper fracture reduction, should be confirmed in future clinical trials.